Pengaruh Budaya Organisasi dan Lingkungan Kerja terhadap Kepuasan Kerja Karyawan - Imamah Imamah; Nursiah Nursiah; Moch. Zainal Achwan; Febri Dwi Syahputra; Rena Febrita Sarie (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
Employee satisfaction is an important factor that can influence organizational productivity and performance. This research aims to analyze the influence of organizational culture and work environment on employee satisfaction. The research method uses a quantitative approach with data collection techniques using questionnaires. The research sample was 50 employees of PT. XYZ. The data analysis technique uses multiple regression analysis and classical assumption tests consisting of normality tests, multicollinearity tests and heteroscedasticity tests. The results of the analysis show that both organizational culture and work environment have a significant positive influence partially and simultaneously on employee satisfaction